Proof of Mens Rea and Actus Reus of Corporate as a Corruption Criminal Actor in Restoration of Criminal Law in Indonesia - Widijowati, Dijan; Darmawan, Halim (International Journal of Psychosocial Rehabilitation, 2020)
Proving mens rea and actus reus corporations as corruptors is not an easy matter, considering that corporations are legal entities. Mens rea is a difficult element to prove from a corporation that is considered to have committed a crime because the corporation can only carry out actions through the organs of directors. When the perpetrator’s actions are said to have fulfilled the formulation of offense (actus reus), then the investigator only needs to see whether the perpetrator has mens rea for the act so that criminal liability can be requested. This study uses interviews and data collection from speakers. The results of the study concluded that the way of proving a corporation in a criminal act of corruption is based on the dichotomy of the legal status between the corporation and the management of the corporation. Proof is done by dividing qualitatively about mens rea and actus reus owned by corporations with corporate management in criminal acts of corruption. The Ius contituendum in corruption is related to the renewal of the criminal law system in Indonesia, which can be done by updating the criminal procedure law which regulates the separation of legal liability between the corporation and the management of the corporation. The application of technical rules regarding the proof of mens rea and actus reus between the corporation and the management of the corporation under the law is considered to be contrary to the protection of the rights / obligations of legal subjects.